2018
DOI: 10.1016/j.tranon.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ADC With Pathological Treatment Response for Radiation Therapy of Pancreatic Cancer

Abstract: PURPOSE: To investigate the feasibility of using apparent diffusion coefficient (ADC) to assesspathological treatment response in pancreatic ductal adenocarcinoma (PDAC) following neoadjuvant chemoradiation (nCR). MATERIALS/METHODS: MRI and pathological data collected for 25patients with resectable and borderline resectable PDAC following nCR were retrospectively analyzed. Pre- and post-nCR mean ADC values in the tumors were compared using Wilcoxon matched pairs test. Correlation of pathological treatment resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…There are differences in tumor margin, enhancement pattern, portal enhancement ratio, and duct dilatation among PNETs 1113. Diffusion-weighted imaging (DWI) or the apparent diffusion-coefficient (ADC) map obtained from DWI is an effective imaging method in assessment of tumors or pathological treatment response to chemoradiation 14,15. Lotfalizadeh et al16 found that mean ADC and diffusion coefficient (D) became significantly lower as tumor grade of PNETs increased.…”
Section: Introductionmentioning
confidence: 99%
“…There are differences in tumor margin, enhancement pattern, portal enhancement ratio, and duct dilatation among PNETs 1113. Diffusion-weighted imaging (DWI) or the apparent diffusion-coefficient (ADC) map obtained from DWI is an effective imaging method in assessment of tumors or pathological treatment response to chemoradiation 14,15. Lotfalizadeh et al16 found that mean ADC and diffusion coefficient (D) became significantly lower as tumor grade of PNETs increased.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been various studies on the potential of changes in ADC values for monitoring treatment response, to the best of our knowledge, there have been no studies on the potential for predicting clinical outcomes in bone metastases. Several studies demonstrated that changes between pre- and post-treatment ADC parameters were correlated with treatment response and clinical outcome in malignant brain tumors [ 31 , 32 ] and pancreatic cancer [ 33 ]. Accordingly, it seems reasonable to assume that there may be associations between changes in ADC parameters after RT and local disease progression in bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at 4 weeks after treatment, the responders revealed a significantly larger percentage increase in the median ADC (10.4%) value of the solid tumor than the nonresponders (−1.15%), which is consistent with literature published on esophageal, rectal, pancreatic, and prostate cancers and myeloma. 19 , 38 , 39 , 40 Such an early indicator of response would clearly be helpful for optimizing treatment management of MPM as patients who are unlikely to respond could be offered other emerging treatments at an earlier time point. Nevertheless, there was no significant change in the TTV in either the responders or nonresponders at 4 weeks after treatment, nor was there a significant correlation between the percentage TTV change at 4 weeks with CT mRECIST tumor measurements at 12 weeks post-treatment.…”
Section: Discussionmentioning
confidence: 99%